Effects of exogenous melatonin on the growth and cadmium accumulation of lettuce under cadmium‐stress conditions. Issue 2 (5th November 2022) - Tang, Wen; Liang, Le; Li, Rulong; Xie, Yongdong; Li, Xiaomei; Li, Huanxiu; Lin, Lijin; Huang, Zhi; Sun, Bo; Sun, Guochao; Tu, Lihua; Tang, Yi
Abstract: Melatonin (MT) is a signaling molecule that is widely present in plants and can help them resist abiotic stresses. In this study, the effects of different concentrations of exogenous MT on the growth and development of lettuce ( Lactuca sativa ) under cadmium stress (50 μmol/L) were investigated. Based on their Cd accumulation differences, the "Hong Feng" and "Luo Ma" lettuce cultivars were selected as research materials. The results showed that different concentrations of MT could promote the growth of lettuce under 50 μmol/L cadmium stress. The application of exogenous melatonin can significantly increase the plant height, biomass, chlorophyll, soluble protein and soluble sugar content of lettuce, and increase the net photosynthetic rate. MT could also reduce the malondialdehyde content in lettuce under cadmium stress and increase the activities of superoxide dismutase, peroxidase, and catalase activities. After treatment with different concentrations of MT, the Cd content in the shoots of both cultivars significantly decreased; in contrast, the Cd content in the roots was significantly increased, which limited the transport of Cd from underground to the shoots. In addition, both Cd stress and exogenous MT induced the synthesis of endogenous MT, and 50 μmol/L MT treatment most effectively induced this response. In conclusion, this study demonstrated that MT could alleviate the negative effects of Cd stress on lettuce with different Cd accumulation differences in terms of physiological indicators. Therefore, it provides a certain reference for the potential of MT to be applied to crops threatened by heavy metals.